A linguagem e o brincar em condições neurodiversas - Oliveira, Jáima Pinheiro de (Editora Oficina Universitária, 2022)
[...] The book Language and Playing in Neurodiverse Conditions, organized by Jáima Pinheiro de Oliveira, Aila Narene Dahwache, Cria Rocha and Ana Paula Loução Martins, which is now being presented to the reading public, is a portrait of the enormous progress that has come occurring in recent decades in this area of investigation and intervention. This advance is characterized by new possibilities such as Alternative and Augmentative Communication and Assistive Technology resources to favor the communication of people with language development problems for a variety of reasons. [...]